2016
DOI: 10.4236/ojms.2016.61010
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Sedimentary Organic Matter and Implication of Its Transfer from Changjiang Estuary to Hangzhou Bay, China

Abstract: In this study, a comparison was made between the Changjiang Estuary and the Hanghzou Bay, in terms of the sources and diagenesis of the sedimentary organic matter (OM). To achieve this purpose, surface sediments from the estuary and bay were analyzed for lignin-derived phenols, stable carbon isotope and TOC/TN (total organic carbon/total nitrogen) molar ratio. The signal of landderived OM decreased, and the vanillic acid to vanillin ratio, (Ad/Al)v, increased with increasing distance from the Changjiang Estuar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The river flux of Changjiang River is more than 20 times that of Qiantang River. In addition, previous hydrological and biomarker research had indicated that CDW may flow into Hangzhou Bay (Qiantang River) and represented the major source of sediment in the Hangzhou Bay (Dai et al, ; Su & Wang, ; Xu et al, ). Thus, Hangzhou Bay water was not considered as an end‐member.…”
Section: Discussionmentioning
confidence: 99%
“…The river flux of Changjiang River is more than 20 times that of Qiantang River. In addition, previous hydrological and biomarker research had indicated that CDW may flow into Hangzhou Bay (Qiantang River) and represented the major source of sediment in the Hangzhou Bay (Dai et al, ; Su & Wang, ; Xu et al, ). Thus, Hangzhou Bay water was not considered as an end‐member.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were stored anoxically on ice in gas-tight bags and were transported to the laboratory within 3 h, where they were kept at 4°C until further treatment. The samples were dominated by silt sediment, which is mainly supplied by the Yangtze River (33) and is considered to be rich in terrigenous organic matter (34).…”
Section: Methodsmentioning
confidence: 99%
“…(c) C/N ratios (Cai et al, 2016;Liu, 2018;Chen et al, 2019;Zhang et al, 2022). (d) C/N ratios in this study and of surface sediments in some bloom areas (Hu et al, 2014;Chao et al, 2017;Wang et al, 2018;Rodil et al, 2020;Wang, 2020b;Likumahua et al, 2021;Xu, 2022;Beltran-Perez et al, 2023). The text above the column indicates different experimental conditions or areas.…”
Section: Discussionmentioning
confidence: 84%